THE AUTHOR AND THE EDITOR – JAN LECHOŃ AND MIECZYSŁAW GRYDZEWSKI IN “WIADOMOŚCI” (1948–1956) - Urbańska, Monika (Prace Polonistyczne, 2025)
The article centres on Jan Lechoń’s work as an editor and proofreader of his own texts, as well as his cooperation in this capacity with Mieczysław Grydzewski. Since 1948, Lechoń published most of his texts (poems, fragments of his diary, and letters) in “Wiadomości”, a periodical edited by Mieczysław Grydzewski. Urbańska examines the author’s attitude to proofreading, the publishing process, the aesthetic and typographic quality of these texts, and their promotion. Urbańska approaches Lichoń’s work from a documentary, source-based perspective. Thus, her research largely focuses on the correspondence between Grydzewski with Lechoń, published by Beata Dorosz. For many years, these letters were their sole means of communication and professional collaboration. Urbańska also looks into the psychological aspects of their relationship as reflected in the letters, which influenced the nature and quality of their editorial work. Lechoń and Grydzewski’s collaboration unfolded against the backdrop of emigrant life: at that time, Lechoń lived in New York, while Grydzewski was based in London. Finally, Urbańska considers the axiological perspective, analyzing the values emerges from the analyzed documents.